2023
DOI: 10.3390/microorganisms11081987
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical, Antioxidant Properties and Antimicrobial Activity of Steno-Endemic Origanum onites

Abstract: Origanum onites (Lamiaceae) is an Eastern Mediterranean plant that is widely used in Turkish traditional medicine. This study aimed to investigate the biochemical composition, antimicrobial activity, and antioxidant potential of O. onites. In this study, the biochemical composition of the O. onites ethanol extract (OOEt) was analyzed using GC-MS. The antimicrobial activity was investigated using a disk diffusion test and determining minimum inhibitory concentrations (MIC) against 30 microorganism strains, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Plants stand out as alternative antimicrobial sources. Studies with O. onites indicated that the extract [24] and essential oil [47][48] of this species have high antimicrobial activity on resistant pathogens. It is known that silver nanoparticles show very strong antimicrobial activity on resistant microorganisms [49].…”
Section: Antimicrobial Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Plants stand out as alternative antimicrobial sources. Studies with O. onites indicated that the extract [24] and essential oil [47][48] of this species have high antimicrobial activity on resistant pathogens. It is known that silver nanoparticles show very strong antimicrobial activity on resistant microorganisms [49].…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…The Origanum onites, belonging to the Lamiaceae family, is a group of plants that grow in the Eastern Mediterranean region and are widely used in the treatment of various diseases in traditional medicine [23][24]. O. onites, known as Turkish thyme, is a perennial and herbaceous plant species [25].…”
Section: Introductionmentioning
confidence: 99%
“…Canly et al [ 2 ] have conducted a study that elucidates the potent antimicrobial properties of an ethanol extract derived from Origanum onites L. (OOEt). This extract has demonstrated significant efficacy against a diverse spectrum of pathogenic microorganisms, including both bacterial and fungal strains.…”
mentioning
confidence: 99%